Influencia del taller de francés en el rendimiento académico de alumnos de tercer año, I.E. “San Juan”, Trujillo, 2018 - Caipo Zavala, Christell Lucero (2019)
The thesis: Influence of the french workshop on the academic performance of third year students, “San Juan” high school, Trujillo, 2018 seeks to determine the influence of the French workshop on the academic achievement of the area._x000D_ The research was quasi-experimental, also, the design selected was correlational. The population is made up of 313 students of 3rd grade in San Juan Emblematic Institution, who were selected for convenience. In the development of the present work, it was applied a pretest; then the French workshop based on the communicative approach comprised in 6 sessions; finally, the post test was developed._x000D_ The results show the level of the students in each language competence: oral comprehension, oral production, written comprehension and written production. Therefore, it is concluded that there is a significant difference between academic performance before and after the application of the workshop. Additionally, certain recommendations are reached for future investigations related to this work.